Improve Pre-Reading Skills of Children with Light Intellectual Impairment with Read Aloud Method - Nurjanah, Inne; Mawardah, Mutia (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
The pre-reading ability is a fundamental skill that must be mastered to improve reading skills. Learning to read requires an understanding of symbols and theoretical comprehension, thus requiring strong imagination and memory. The learning process can be challenging to be quickly grasped by mildly intellectually disabled children with learning disabilities. Although the cognitive abilities of mildly intellectually disabled children may be slow, they can still be gradually developed with an effective learning process, such as the read-aloud method, to make children comfortable with reading activities, thus facilitating the gradual acceptance of pre-reading learning. This research aims to determine the influence of the read-aloud method on pre-reading abilities in mildly intellectually disabled children at SLB-C Autis Pelita Hati Palembang. The research method used is experimental quantitative. Sample selection is done using purposive sampling technique, with a sample size of 6 mildly intellectually disabled students. Data collection methods include interviews, observations, questionnaires, and measurements using a modified pre-reading ability assessment test assessed using the Guttman scale. The design used in this research is a repeated treatment design with a one-group pretest-posttest design. The data analysis technique used is the paired sample t-test. The hypothesis testing results show t = -18.634 and p = 0.000, indicating that p < 0.05, which means the hypothesis is accepted. This indicates that there is a difference between the pre-test and post-test results after the read aloud treatment, meaning that reading aloud influences the pre-reading abilities of children with mild hearing impairments.Kemampuan pra-membaca merupakan hal dasar yang harus dikuasai untuk meningkatkan kemampuan membaca. Dalam pembelajaran membaca membutuhkan pemahaman simbol dan pemahaman secara teoritis, sehingga membutuhkan daya imajinasi dan daya ingat yang kuat. Proses pembelajaran tersebut sulit untuk cepat diterima bagi anak tungarahita ringan yang memiliki keterbatasan intelektual. Meskipun kemampuan dalam berpikir anak tunagrahita ringan lambat, namun masih dapat dikembangkan secara perlahan dengan proses pembelajaran yang efektif yaitu dengan metode read aloud agar anak nyaman dengan kegiatan membaca sehingga perlahan proses belajar pra-membaca dapat mudah diterima. Penelitian ini bertujuan untuk mengetahui pengaruh read aloud terhadap kemampuan pra-membaca pada anak tunagrahita ringan di SLB-C Autis Pelita Hati Palembang. Metode penelitian yang digunakan dalam penelitian ini yaitu metode kuantitatif eksperimental. Pengambilan sampel menggunakan teknik purposive sampling dengan jumlah sampel 6 siswa tunagrahita. Metode pengumpuan data melalui wawancara, observasi, angket dan alat ukur berupa modifikasi tes asesmen kemampuan pra-membaca dengan cara penilaian menggunakan skala guttman. Desain yang digunakan dalam penelitian ini adalah desain perlakukan ulang dengan one group pretest-posttest design. Teknik analisis data menggunakan uji paired sample t-test. Hasil pengujian hipotesis menunjukkan t = -18,634 dan p = 0,000 sehingga p< 0,05 yang berarti hipotesis diterima. Hal ini menunjukkan bahwa terdapat perbedaan hasil pre-test dan post-test setelah treatment read aloud yang artinya read loud memiliki pengaruh terhadap kemampuan pra-membaca pada anak tungarhita ringan.